Evaluation of Non-Saccharomyces Cerevisiae Strains Isolated from Sea Water Against Inhibitory Compounds for Ethanol Production - Thontowi, Ahmad; Putra, Filemon Jalu Nusantara; Yopi, Yopi (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2017)
An important parameter in industrial bioethanol fermentation is the resistance of yeast to osmotic pressure and inhibitor compounds. Aureobasidium pullulans LBF-3-0074 and Schwanniomyces etchellsii LBF-3-0034 are reported capable to produce ethanol. LBF-3-0034 and LBF-3-0074 are yeast strains isolated from Bali and Lombok sea water. This study aimed to evaluate characteristics of both LBF-3-0034 and LBF-3-0074 strains under the effects of glucose and inhibitor compounds. Both strains were allowed to consume glucose up to 120 mM. Then, these strains were grown with the present of several inhibitors, i.e. 5-hydroxymethyl-2-furaldehyde (5-HMF), furfural, acetic acid, formic acid, and levulinic acid. Results showed that the two yeast strains studied could grow and ferment the sugars under both osmotic and inhibitor stress conditions. As conclusion, Schwanniomyces etchellsii LBF-3-0034 and Aureobasidium pullulans LBF-3-0074 are potential for direct fermentation of lignocellulosic hydrolysate to ethanol.